KONSEP FITRAH SEBAGAI POTENSI MANUSIA DAN IMPLIKASINYA TERHADAP PENDIDIKAN ISLAM - Miftahul Huda; Nurwadjah Ahmad; Andewi Suhartini (Journal of Research and Thought on Islamic Education (JRTIE), 2021)
This study aims to examine the concept of fitrah as human potential in the process of Islamic education. The research approach used in this study is a qualitative research approach, with library research data collection techniques, namely the author collects library data related to this research to be able to answer the problems specified. Based on the results of the study, it can be concluded that fitrah is a human potential given by Allah SWT in the form of sight, hearing, and heart, all of which are related to one another. Hearing is in charge of maintaining the knowledge that has been obtained from the teaching and learning process, vision is in charge of developing and adding knowledge from the results of research and study, while the heart is in charge of cleaning science from all bad qualities. Keywords: Fitrah; Human Potential; Islamic Education